PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SD NEGERI 004 SALO KECAMATAN SALO KABUPATEN KAMPAR - yuniati, Citra; Marhadi, Hendri; Alim, Jessi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : This research aims to improve learning outcomes Natural Sciences graders Elementary School VB 004 Salo Salo District of Kampar in the school year 2014/2015 through "inquiry learning model". This research was conducted in March until the month of April 2015. The number of students of class VB 23 people, consisting of 8 male students and 15 female students. This research is a class act that contains two cycles. Each cycle consists of 2 meetings and one-time daily tests. The research instrument consists of learning tools (syllabi, lesson plans, Student Worksheet, activity observation sheet of students and teachers). The research data will be analyzed descriptively. The research data show that the learning outcomes IPA graders Elementary School VB 004 Salo Salo District of Kampar increased. Before the implementation of inquiry learning model, based on the base score of students who reach KKM (65) only 9 people with a percentage of 39.13%. But after using the application inquiry learning model on the first daily test the first cycle, the number of students who reach KKM risen to 13 people with a percentage of 56.52%. While the second repetition in the second cycle, students who achieve KKM increased again to 18 people with a percentage of 78.26% .Then activity of students during the learning process in the first cycle of the first meeting with the percentage categorized as less than 62.5%, and the second meeting of the the first cycle can be categorized simply by percentage of 68.75%. While the activity of students in the second cycle the first meeting can be categorized either by a percentage of 83.33% and at the meeting of the two can also be categorized very well because the percentage reached 93.75%. While the activities of teachers in the first cycle with the first meeting categorized enough percentage value 62.5% and at the meeting of the two increased to 68.75% with the category enough. At the first meeting of the second cycle of activity can be said to be a good teacher with a percentage value as much as 83.33% and at the meeting of the two increased to 93.75% with very good category. Classes have been completed can be said for having mancapai 75% of the number of students who pass. From the above shows that the implementation of inquiry learning model can improve learning outcomes VB grade science students of SD Negeri 004 Salo Salo District of Kampar.Key word : inquiry learning model, outcomes of IPA